Pretext: concept and peculiarities of functioning in the communicative act - Синявська, Леся Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
This article analyzes the peculiarities of the dramatic text in the communicative act. Variants of the dramatic text are distinguished – written and stage, stage text devision into replicas and secondary, minor text that forms the metatext. In the written version of the dramatic text the pretext includes series, publisher, author guidelines, the character of the author’s alias, title, author’s instructions and the nature of the text, instructions and genre, ways of division of the text, personalized / impersonalized text, the nature of the initial line, division into acts, scenes, list of the actors, remarks.